Traditional Health Practices In The Kajang Community: Health Practices - Fhyra, Musfirah; Kamaruddin, Syamsu Andi; Adam, Arli; Ihsan, Andi; Hasma, Hasma (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2024)
Background: Practice health traditional has become an integral part of culture and identity public Kajang, a group ethnic groups living in the interior of Borneo. In an attempt For guard health and well-being them, society Awning has develop series a practice that is hereditary and rooted in trust tradition and wisdom local. Methods: Study This aim For explore and understand practice health traditionally used by the community Kajang. Through approach involving qualitative observation participative and interview deep with member community. Results: Research result show that practice health traditional public Awning involve use herbal concoctions and traditional rituals ceremony traditional purpose For cure body and recover spiritual balance. Apart from that, practices this also became means For strengthen connection social in community and care sustainability culture and traditions they. Challenge in preservation and development practice health traditional this, including decline interest generation youth and lack access to source Power naturally required. Conclusions: Therefore,  the research  suggests a number of recommendation For support preservation and revitalization practice health traditional in modern context, including education based health culture and collaboration between practitioner traditional and professional modern health .